Reducing surgical mortality in Scotland by use of the WHO Surgical Safety Checklist. Issue 8 (16th April 2019) - Ramsay, G.; Haynes, A. B.; Lipsitz, S. R.; Solsky, I.; Leitch, J.; Gawande, A. A.; Kumar, M.
Abstract : Background: The WHO Surgical Safety Checklist has been implemented widely since its launch in 2008. It was introduced in Scotland as part of the Scottish Patient Safety Programme (SPSP) between 2008 and 2010, and is now integral to surgical practice. Its influence on outcomes, when analysed at a population level, remains unclear. Methods: This was a population cohort study. All admissions to any acute hospital in Scotland between 2000 and 2014 were included. Standardized differences were used to estimate the balance of demographics over time, after which interrupted time‐series (segmented regression) analyses were performed. Data were obtained from the Information Services Division, Scotland. Results: There were 12 667 926 hospital admissions, of which 6 839 736 had a surgical procedure. Amongst the surgical cohort, the inpatient mortality rate in 2000 was 0·76 (95 per cent c.i. 0·68 to 0·84) per cent, and in 2014 it was 0·46 (0·42 to 0·50) per cent. The checklist was associated with a 36·6 (95 per cent c.i. –55·2 to –17·9) per cent relative reduction in mortality ( P < 0·001). Mortality rates before implementation were decreasing by 0·003 (95 per cent c.i. –0·017 to +0·012) per cent per year; annual decreases of 0·069 (–0·092 to –0·046) per cent were seen during, and 0·019 (–0·038 to +0·001) per cent after, implementation. No such improvement trends were seen in the non‐surgical cohort over this time frame. Conclusion: Since the implementation of the checklist, as part of an overall national safety strategy, there has been a reduction in perioperative mortality. Abstract : The WHO surgical safety checklist has been widely implemented since its launch in 2008. Its influence on outcomes, however, when analysed at a population level, remains unclear. This population cohort study noted a reduction in perioperative mortality rates after implementation of the checklist as part of a wider national strategy on patient safety. The checklist is effective